TRIBUTO A URSULA K. LE GUIN: Testemunhos de Vários Escritores, Artistas e Professores - Vários (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
To close this issue, I thought that a tribute to Ursula K. Le Guin of our own was absolutely necessary. Therefore, various writers, artists and professors were invited to submit a personal/professional statement describing the influence Le Guin’s work has had on their own work. I would like to thank each one of them for their words of praise, for they have proven that Ursula K. Le Guin lives beyond the Anglo-American literary context and lives beyond her years, inspiring us to lead our lives with critical thinking, imagination and respect for the Other.